Investigating The Alkalizing Potential of Chandanasava For Restoring Acid-Base Homeostasis in Renal Tubular Acidosis: A Computational and In Silico Pharmacological Study - Nandana V A (International Journal of Bioinformatics and Computational Biology, 2025)
Chandanasava, a traditional Ayurvedic formulation, is recognized for its potential alkalizing properties, which may help restore acid-base homeostasis in conditions such as renal tubular acidosis (RTA). This study aims to investigate the active components of Chandanasava and their interactions with key renal target proteins, Pendrin and Carbonic Anhydrase II, which are essential for maintaining acid-base balance. An in silico approach was utilized to explore the pharmacological potential of the phytochemicals present in Chandanasava as therapeutic agents for RTA. We got the protein structures from the RCSB Protein Data Bank and the ligands from the IMPPAT database. ADME (Absorption, Distribution, Metabolism, and Excretion) analysis was performed using SwissADME to evaluate the pharmacokinetic properties of the ligands. Protein purification was conducted using Biovia Discovery Studio, where non-structural atoms were removed and validated using the Ramachandran plot. Molecular docking studies were performed using PyRx to assess the binding affinities between the phytochemicals and the target proteins. Post-docking analysis was carried out in Biovia Discovery Studio to obtain 3D and 2D structures and to evaluate non-bonded interactions between the amino acids. A total of 67 active components from Chandanasava were identified and analyzed for their binding interactions with Pendrin and Carbonic Anhydrase II. The results revealed that several ligands exhibited strong binding affinities to the target proteins, with binding scores ranging from -9.3 to -9.5 kcal/mol considered significant for further investigation. Notably, Proximadiol and 3,6-Bis(benzo[d][1,3]dioxol-5-yl)tetrahydro-1H,3H-furo[3,4-c]furan-1,4-diol demonstrated the highest binding affinities for Carbonic Anhydrase II and Pendrin respectively, indicating their potential as targeted therapies for restoring acid-base homeostasis in RTA. The findings of this study suggest that the active components of Chandanasava may represent promising candidates for the development of new therapeutic strategies for renal tubular acidosis. This research provides a foundation for future experimental studies to validate the efficacy of these phytochemicals in clinical applications.
Keywords: Carbonic Anhydrase II; Chandanasava; Pendrin; Phytochemicals; acid-base homeostasis; molecular docking; renal tubular acidosis